2012
DOI: 10.1038/bjc.2012.126
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic equilibrium between cancer stem cells and non-stem cancer cells in human SW620 and MCF-7 cancer cell populations

Abstract: Background:Cancer stem cells (CSCs) paradigm suggests that CSCs might have important clinical implications in cancer therapy. Previously, we reported that accumulation efficiency of CSCs is different post low- and high-LET irradiation in 48 h.Methods:Cancer stem cells and non-stem cancer cells (NSCCs) were sorted and functionally identified through a variety of assays such as antigen profiles and sphere formation. Inter-conversion between CSCs and NSCCs were in situ visualised. Cancer stem cells proportions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 35 publications
(66 reference statements)
9
122
1
Order By: Relevance
“…The phenotypic plasticity of CSCs is dynamically regulated by intrinsic and extrinsic signals originating from the cancer microenvironment. TGF-␤, a major inducer of EMT, has an important role in the inter-conversion and equilibrium of CSCs and non-CSCs by regulating the EMT process (33). Indeed, we found that TGF-␤ was up-regulated in HA-overproducing cancer cells and that the inhibition of its signaling pathway significantly reduced EMT and CSC conversion.…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expmentioning
confidence: 68%
“…The phenotypic plasticity of CSCs is dynamically regulated by intrinsic and extrinsic signals originating from the cancer microenvironment. TGF-␤, a major inducer of EMT, has an important role in the inter-conversion and equilibrium of CSCs and non-CSCs by regulating the EMT process (33). Indeed, we found that TGF-␤ was up-regulated in HA-overproducing cancer cells and that the inhibition of its signaling pathway significantly reduced EMT and CSC conversion.…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expmentioning
confidence: 68%
“…The initial 200 nm aggregates formed by the relatively rapid nucleation of Zn−hexamer subsequently grow through the further addition of Zn− hexamer to these aggregates, that is, via "nucleation and growth". 55,56 Increase of the temperature to 37°C does not appear to change the mechanism of aggregation but results in a modest increase in the apparent diameter and final turbidity (data not shown). This is consistent with other observations of Zn−insulin aggregating at pH 4−9, although aggregate size did not exceed 20 nm diameter (at I = 100 mM).…”
Section: 53mentioning
confidence: 91%
“…Similar observations linking plasticity and EMT have been made in cell lines [36]. More recently, Yang et al [37] have visualised plasticity between non-stem cancer cells and bCSCs occurring in situ in MCF-7 cells and shown that this process could be enhanced by the induction of EMT or perturbed by its inhibition [37].…”
Section: Plasticity Of Breast Cancer Stem-like Cells Plasticity Betwementioning
confidence: 55%